Implantação da gestão da qualidade em uma pequena empresa de base tecnológica por meio de pesquisa-ação - Gonçalves, Marcos Pereira (Universidade Federal de São Carlos, 2010)
Quality management is showing as one of the main strategies for organizations competitiveness capacity increase, mainly in a dynamic market environment point by a hard competition between products and services suppliers. The quality management relevance did result in a diffusion of concepts, techniques, standards and models aimed to orient such systems implementation, as the ISO 9001 - 2000 reference model each has been widely adopted by organizations. However quality management system implementation is a challenger task where the success depends on a consistent managing effort and a priority strategy aligned to the specific features of each organization. The technology based enterprises has specific features that indicates the ability to absorb new knowledge and priority for technology strategy associated to the new products and process development. This research presents the quality management implementation process in a technology based company, approaching the planning and the more relevant actions in the context of those typical company features, specially the product development process, the performance measurement system, and continuous improvement systems. The action research methodology has been adopted as it is a participative method that enables to achieve the practical objectives, quality management implementation, and the knowledge objectives about the action development. The implementation process observation unveils the main difficulties and solutions founded in order to attend the company demands. As a contribution, the observation analysis in the context of the theoretical background enables to build a correlation between those company features and the quality management system implementation needs, in a way to consolidate a proposal for a specific conceptual perspective for quality management system for other similar companies. As a practical result, the quality management system implementation brought effective gains in productivity measured by the main company performance indicators.
Keywords: Gestão da qualidade; ISO 9001; Empresas de base tecnológica; Melhoria contínua; Quality management; ISO 9001-2000; Technology based enterprise; Continuous improvement; ENGENHARIAS::ENGENHARIA DE PRODUCAO